Kajian Pengunaan Static Mixing Reactor Pada Proses Produksi Biodiesel Secara Katalitik Dengan Sistem Continue - Christian Soolany; Armansyah H. Tambunan; R Sudradjat (Jurnal Penelitian Hasil Hutan, 2015)
Production of biodiesel catalytically requires catalyst and stirring. Good stirring system will produce a homogeneous mixture between triglycerides and methanol. Good stirring can be generated with the use of static mixers. This paper studies the static mixing reactor with continuous system in production of biodiesel catalytically and optimizing the length of static mixer in order to obtain methyl ester level based on standard. The experiments were conducted with transesterification method using palm olein (RBDPO) and methanol with molar ratio 1:6, KOH catalyst of 0.5% and the reaction temperature of 65°C. Biodiesel production process used transient condition. Biodiesel production process with catalyst used two models of static mixer. The treatment was the length of the static mixer. The variations of the static mixer length were conducted by passing fluid one time through static mixer reactor after the temperature has been reached (A0 = 2 static mixer), passed two times through the static mixer reactor (A1 = 4 static mixers), passed three times through the static mixer reactor (A2 = 6 static mixers), and passed four times through the static mixer reactor (A3 = 8 static mixers). Results show that for each treatment had produced methyl ester content above the standard of 96.5% w/w. The determination of the best treatment was obtained based on the best value for parameters of methyl ester and total glycerol resulted was on the condition of 4 times passed in the static mixer reactor (A3 = 8 static mixers) which produced methyl ester content of 97.92% w/w, total glycerol of 0.85%, acid number of 0.31 mg KOH/g, saponification number of 202 mg KOH/g, the biodiesel yield of 98.26%, and reaction time 29 minute.